Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure, let's solve for the missing numbers step-by-step.
1. Let's start with the sequence and the operations involved in deriving the missing numbers:
[tex]\[ \begin{array}{cccc} 1 & -3 & -10 & 24 \\ & b & d & \\ 1 & c \end{array} \][/tex]
2. Finding [tex]\( b \)[/tex]:
Based on the sequence, the relationship given is:
[tex]\[ 2 \times 1 + a = b \][/tex]
From the given array, [tex]\( a = -3 \)[/tex]:
[tex]\[ 2 \times 1 + (-3) = b \][/tex]
Solving that:
[tex]\[ 2 - 3 = -1 \][/tex]
Therefore:
[tex]\[ b = -1 \][/tex]
3. Finding [tex]\( c \)[/tex]:
The next relationship is:
[tex]\[ 2 \times (-3) + b = c \][/tex]
Substitute [tex]\( b = -1 \)[/tex]:
[tex]\[ 2 \times (-3) + (-1) = c \][/tex]
Solving that:
[tex]\[ -6 - 1 = -7 \][/tex]
Therefore:
[tex]\[ c = -7 \][/tex]
4. Finding [tex]\( d \)[/tex]:
The final relationship is:
[tex]\[ 2 \times (-10) + c = d \][/tex]
Substitute [tex]\( c = -7 \)[/tex]:
[tex]\[ 2 \times (-10) + (-7) = d \][/tex]
Solving that:
[tex]\[ -20 - 7 = -27 \][/tex]
Therefore:
[tex]\[ d = -27 \][/tex]
So the missing numbers are:
[tex]\[ \begin{aligned} b &= -1 \\ c &= -7 \\ d &= -27 \end{aligned} \][/tex]
1. Let's start with the sequence and the operations involved in deriving the missing numbers:
[tex]\[ \begin{array}{cccc} 1 & -3 & -10 & 24 \\ & b & d & \\ 1 & c \end{array} \][/tex]
2. Finding [tex]\( b \)[/tex]:
Based on the sequence, the relationship given is:
[tex]\[ 2 \times 1 + a = b \][/tex]
From the given array, [tex]\( a = -3 \)[/tex]:
[tex]\[ 2 \times 1 + (-3) = b \][/tex]
Solving that:
[tex]\[ 2 - 3 = -1 \][/tex]
Therefore:
[tex]\[ b = -1 \][/tex]
3. Finding [tex]\( c \)[/tex]:
The next relationship is:
[tex]\[ 2 \times (-3) + b = c \][/tex]
Substitute [tex]\( b = -1 \)[/tex]:
[tex]\[ 2 \times (-3) + (-1) = c \][/tex]
Solving that:
[tex]\[ -6 - 1 = -7 \][/tex]
Therefore:
[tex]\[ c = -7 \][/tex]
4. Finding [tex]\( d \)[/tex]:
The final relationship is:
[tex]\[ 2 \times (-10) + c = d \][/tex]
Substitute [tex]\( c = -7 \)[/tex]:
[tex]\[ 2 \times (-10) + (-7) = d \][/tex]
Solving that:
[tex]\[ -20 - 7 = -27 \][/tex]
Therefore:
[tex]\[ d = -27 \][/tex]
So the missing numbers are:
[tex]\[ \begin{aligned} b &= -1 \\ c &= -7 \\ d &= -27 \end{aligned} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.